Data resource profile: the disability statistics questionnaire review database (DS-QR Database): a database of population censuses and household surveys with internationally comparable disability questions - Bradley Carpenter; Sureshkumar Kamalakannan; Pavani Saikam; David Vicente Alvarez; Jill Hanass-Hancock; GVS Murthy; Monica Pinilla-Roncancio; Minerva Rivas Velarde; Douglas Teodoro; Sophie Mitra (International Journal of Population Data Science)
Introduction The 2030 Sustainable Development Agenda and the United Nations Convention on the Rights of Persons with Disabilities (CRPD) aspire to leave no one behind and call for the inclusion of persons with disabilities in all spheres of life. To monitor this goal of inclusion, CRPD's Article 31 requires state parties to collect data about the situation of persons with disabilities. The Disability Statistics -- Questionnaire Review Database (DS-QR Database) reports on whether population and housing censuses and household surveys include internationally recommended disability questions for adults ages 15 and older.